Peran Citicoline pada Anak Pasca-Operasi Otak - Lina Purnamasari (PT Kalbe Farma Tbk., 2024)
Citicoline is a drug that has many benefits as a neuroprotector. Many studies in adults show the clinical benefits of citicoline in various neurological disorders such as dementia, head trauma, stroke, Parkinson, etc. However, the effectiveness of citicoline in children has not been widely studied.